Pasture legumes differ in herbage production and quality throughout spring, impacting their potential role in fodder conservation and animal production. (25th March 2021) - Hackney, Belinda; Rodham, Craig; Dyce, Gabrielle; Piltz, John
Abstract: This study reports on the herbage production and quality of a range of pasture legume species during spring, at three sites with moderate to strongly acidic soils in southern NSW, Australia. These data have enabled prediction of livestock production when legumes are conserved as silage or hay. Total herbage production, its timing and quality differed significantly between species, which generally was not predicted by the traditional metric of time to flowering. Trifolium incarnatum L., T. michelianum L., Biserrula pelecinus L., Ornithopus sativus Brot. and Hedysarum coronarium L. all maintained growth rates exceeding 200 kg DM/ha/d for 4 weeks over spring, while T. vesiculosum Savi. maintained this for 6 weeks, with a peak growth rate of 561 kg DM/ha/d. Herbage quality of all species declined over time and was greatest in species with a rapid increase in stem‐to‐leaf ratio or with weak stems, resulting in lodging. The modelling inferred that maximizing potential livestock production via fodder conservation required earlier cutting. Only the indeterminate species B. pelecinus and Ornithopus spp. increased potential liveweight gain per hectare through delayed harvesting from (probable) silage to hay‐making time.